Indicators of Youth Involvement in Internet Fraud: An Inquiry Among Detained and Convicted Internet Fraudsters in Ogun State Correctional Facilities, Nigeria - DAMILOLA, Akinpelumi; MUYIDEEN, Ogunmefun Folorunsho; OOREOFE, Ogunnowo Ruth (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:Youth all over the world are known as the dynamic bedrock and cornerstone of nation-building. However, once they are deprived of enjoying their fundamental rights, they easily embrace negative conditions such as cybercrime, civil unrest, psychological trauma, and retrogressive economic development, among others. Extant literature was reviewed for the study with the use of strain and rational choice theories. The study was conducted in four correctional facilities in Ogun State, Nigeria, where detained and convicted internet fraudsters were remanded.Methodology:A mixed method and descriptive research design were adopted for the study. Two hundred and eighty-four inmates (284) were interviewed using structured questionnaires, while 10 interviews were conducted among the inmates using in-depth interviews. Probability (Simple Random) and non-probability (Purposive) sampling techniques were adopted.Findings:All ethical factors were observed the study concluded that most youth who engaged in internet fraud were the product of extreme poverty and unemployment rate among the Nigerian youths. It is therefore recommended that collective efforts from the government, public members and nongovernmental organizations must be channeled towards the provision of employment.Implication:Also, youth should purge themselves from negative innovation to positive innovation to promote the national and international image of the country. However, the study shows that the public awareness campaigns by the government are not reaching the target audience of youths most susceptible to internet fraud.